The Composition of Vesicles of Non-Toxigenic Vibrio cholerae Strains, O1 El Tor and O139 Serogroups - O. V. Duvanova; E. S. Shipko; R. V. Pisanov; O. A. Tsyrulina; O. S. Chemisova; V. V. Evdokimova; A. S. Vodop’yanov; V. D. Kruglikov; I. A. Ivanova; N. D. Omel’chenko; A. V. Filipenko; A. K. Noskov (Проблемы особо опасных инфекций, 2024)
The aim of the work was to study the composition of vesicle preparations (OMV) in Vibrio cholerae strains O1 El Tor (ctxAB– tcpA– ; ctxAB– tcpA+ ) and O139 (ctxAB– tcpA– ) isolated from various sources. Materials and methods. V. cholerae strains O1 and O139 serogroups were used in the work, from which OMV preparations were obtained. The structure of OMV preparations was studied by transmission electron microscopy (TEM). Genome-wide DNA sequencing was performed on the MiSeq platform. The nucleotide and corresponding amino acid sequences of the genes were studied using bioinformatics analysis. Protein profiling was conducted using MALDI-TOF mass spectrometry. Enzymatic activities were detected using appropriate media and substrates. Determination of (surface determinants) lipopolysaccharide (LPS) and outer membrane proteins in the composition of OMV was carried out by enzyme immunoassay (ELISA). The analysis of the spectrum of fatty acids was performed by gas-liquid chromatography mass spectrometry. Results and discussion. OMV preparations have been obtained from non-toxigenic strains of cholera vibrios. TEM has revealed that OMVs are represented by spherical structures of about 40–200 nm. Genome-wide sequencing has shown that fragments of chromosomes containing genes of V. cholerae strains, O1 and O139 serogroups, from which they were isolated are present in the OMV. The bioinformatic analysis revealed differences in the structure of the ompT gene in the initial strains and in OMV obtained from V. cholerae strains O1 and O139 serogroups. The ΔompT gene of the OMV preparation from V. cholerae O139 serogroup was trunked and formed a peptide of 17 amino acid residues (-LENHHQKNREPDKEFPY-). Analysis of the OMV composition has revealed the presence of enzymes (N-acetyl-β-D-glucosaminidase and DNAazes), proteins of outer membranes (ompT and OmpU), LPS, saturated, сis/trans isomers of unsaturated fatty acids and branched fatty acids. Differences in the composition of OMV obtained from non-toxigenic strains of V. cholerae O1 and O139 serogroups have been identified.